The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/rda.13230
|View full text |Cite
|
Sign up to set email alerts
|

Sperm cryopreservation in the Far‐Eastern wildcat (Prionailurus bengalensis euptilurus)

Abstract: The Far-Eastern wildcat (Prionailurus bengalensis euptilurus) is a rare and poorly investigated nondomestic felid species. An attempt of freezing and cryopreserving Far-Eastern wildcat spermatozoa in CaniPlus Freeze (CPF) medium is reported. Sperm was collected by electroejaculation from five adult Far-Eastern wildcat captive-born males. Epididymal spermatozoa from five adult randomly bred domestic cat males were used as a reference. The viability of frozen-thawed spermatozoa evaluated by double staining with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Laboratory models are needed for wild species, as they allow us to develop the basis for techniques that later can be adapted to the special requirements of a target species if needed [48]. We already showed that techniques developed in the domestic cat can be successfully applied to wild cats [49][50][51]. Samples from wild cats are extremely rare and cannot be used for basic research.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory models are needed for wild species, as they allow us to develop the basis for techniques that later can be adapted to the special requirements of a target species if needed [48]. We already showed that techniques developed in the domestic cat can be successfully applied to wild cats [49][50][51]. Samples from wild cats are extremely rare and cannot be used for basic research.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei staining with subsequent cell number counting makes it possible to assess felid embryo development (Amstislavsky et al., 2018). Moreover, the percentage of nuclear fragmentation is taken as a measure of the nuclear integrity and embryo development (Amstislavsky et al., 2015; Brison & Schultz, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…To perform these analyses after IVC, embryos were fixed in one mL of DPBS with 4% formaldehyde at pH 7.4-7.6. After fixation, embryos were stained with DAPI, as described earlier (Amstislavsky et al, 2015(Amstislavsky et al, , 2018. Slides with embryos were analysed under LSM 780 NLO AxioObserver Z1 (Carl Zeiss, Germany) with filters suitable for DAPI.…”
Section: Dapi Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the reproductive biology of the Javan leopard have never been reported, unlike in several other wild cats, including the Indian [5], Arabian (P. pardus nimr) [6], and the Indochina (P. pardus delacouri) leopard [7]. Semen cryopreservation efforts in wild cats such as the jaguar (Panthera onca) [8], clouded leopard (Neofelis nebulosa) [9], Prionailurus bengalensis euptilurus [10], and the Sunda clouded leopard (Neofelis diardi) [11] have been reported. A sperm bank/genome bank is a vital step and effort for longterm wildlife conservation [12].…”
Section: Introductionmentioning
confidence: 99%